2012
DOI: 10.1097/aud.0b013e3182498c41
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Ecological Momentary Assessment of Hearing Difficulties Encountered by Hearing Aid Users

Abstract: Objectives Measurement of outcomes has become increasingly important to assess the benefit of audiologic rehabilitation, including hearing aids, in adults. Data from questionnaires, however, are based on retrospective recall of events and experiences, and often can be inaccurate. Questionnaires also do not capture the daily variation that typically occurs in relevant events and experiences. Clinical researchers in a variety of fields have turned to a methodology known as ecological momentary assessment (EMA) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 36 publications
5
60
1
Order By: Relevance
“…In total, 991 assessments were completed. Because the participants showed high compliance (77% response rate to the PDA alarm) and reported positive feedback, the study by Galvez et al (2012) supported the feasibility of computerized EMA. Due to the recent advancement of smartphone technology, applications/software that allow researchers to implement the EMA methodology using smartphones in outcome research has been developed (Hasan et al, 2013).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…In total, 991 assessments were completed. Because the participants showed high compliance (77% response rate to the PDA alarm) and reported positive feedback, the study by Galvez et al (2012) supported the feasibility of computerized EMA. Due to the recent advancement of smartphone technology, applications/software that allow researchers to implement the EMA methodology using smartphones in outcome research has been developed (Hasan et al, 2013).…”
Section: Introductionmentioning
confidence: 73%
“…It would be beneficial to establish and validate a set of standardized questions that can be used in EMA. Finally, it has been suggested that EMA data could be useful for clinicians to understand patients’ specific communication needs, optimize hearing aid fitting, and provide individualized aural rehabilitation training (Galvez et al, 2012). However, the current format of EMA is not suitable for clinical use due to its high levels of respondent load (Kahneman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce the time between a given situation and the questionnaire, the method of ecological momentary assessment (EMA) was introduced. EMA allows to get ongoing data through self-reports, often implemented as the expe- * Supported by governmental funding initiative "Niedersächsisches Vorab" of the Lower Saxony Ministry for Science and Culture, research focus "Hören im Alltag Oldenburg (HALLO)" rience sampling method (ESM) [8], e.g., for hearing aid users [4]. The results are still on subjective scales.…”
Section: Introductionmentioning
confidence: 99%